Climate policy integration in a land use system with ecological thresholds - Martin Lopez (Economic and Environmental Studies (E&ES), 2019)
The land use sector is an area with high potential to pursue mitigation and adaptation goals alike. However, due to the complexity derived from managing landscapes with multiple objectives and the lack of tools to assess the outcome, this potential is presumably subtilized in practice. In order to contribute to fill in this knowledge gap, this paper analyzes climate policy integration -the joint implementation of mitigation and adaptation measures- in the presence ecological thresholds. Based on a hypothetical yet realistic economic-ecologic system, the synergic properties of different isolated and integrated policy configurations were analyzed using a dynamic optimization framework and simulation tools. The results indicate that, regardless of specific circumstances (e.g. observing or not a regime shift), the configuration that better compiled with the definition of a synergy corresponded to a cross sectorial approach: an intervention involving coordination between agriculture and forestry. This result suggests that harmonization among the elements that compose the land use sector is the main source of an enhanced policy outcome. Thus, effective integration requires looking at the land use sector as an entity (e.g. a landscape) rather than isolated components (e.g. agriculture and forestry sectors).
Keywords: Q24; Q23; 330; Mitigation; Adaptation; Climate Policy Integration; Deforestation; Resilience